Recovery capabilities of Xenopus laevis after exposure to Cadmium and Zinc. (November 2015) - Mouchet, F.; Teaniniuraitemoana, V.; Baudrimont, M.; Daffe, G.; Gauthier, L.; Gonzalez, P.
Highlights: Recovery capabilities of Xenopus after 12 days of exposure to Cd and Zn are studied. Genotoxicity, accumulation and additive effect of Cd and Zn are observed after 12 days. MT synthesis and adaptative responses are also observed after 12 days. The recovery of Xenopus larvae occurred after just 7 days of depuration. Their toxic impacts were reversible. Abstract: The present investigation evaluates the recovery capabilities of Xenopus laevis following 12 days of exposure to 30 μg Cd L −1 and 1000 μg Zn L −1 alone or mixed, followed by a depuration phase in laboratory conditions. Focused endpoints, which were investigated at different times of depuration, are bioaccumulation of Cd and Zn, micronucleus induction, quantification of metallothioneins (MTs), and expression of genes involved in metal toxicity mechanisms. The results show that at the end of the contamination phase, there was higher metal bioaccumulation capability and MT synthesis in remaining tissues than in the liver. An increased expression of genes involved in detoxification and oxidative stress mechanisms was observed, suggesting an additive effect of both metals and a higher Zn regulation in the liver. During the depuration phase, the results show the recovery capability of Xenopus from 7 days of depuration related to metamorphosis processes, which were observed at the end of the experiment. The results confirm the relevance of the amphibian model and the complementarities between a marker of genotoxicity, MT production, bioaccumulation and transcriptional analysis in the evaluation of the ecotoxicological impact. The results also highlight the reversible effects of Cd and Zn toxicity.